STATEMENT FOR JACK GANNON, PRESIDENT, IAFF FIRE SAFE CIGARETTE PRESS CONFERENCE (Tufts Archival Research Center, 2007)
Draft; Confidential; Statement by Jack Gannon, President of the International Association of Fire Fighters (IAFF), at a Fire Safe Cigarette Press Conference, commending efforts to determine the feasibility of a fire safe cigarette. Thanks Senator Joe Moakley for his efforts in fire safety but says that there is still a lot to do.